The evaluation of body composition and anthropometric measurements of males aged 18-25 years, based on the regularity of physical exercise - Aksoy, Aziz; Selen, Halime (Progress in Nutrition, 2018)
There were 200 participants in total, on a voluntary basis in the study.  Of these participants, 100 were male students aged 18-25 years who exercised regularly and vigorously, and 100 were male aged 18-25 years who did not participate in any physical activity. The measurements of BMI, body fat composition, hip-to-waist ratio, and skinfolds measured at nine different anatomical areas of their bodies (pectoral, biceps, triceps, subscapular, abdominal, suprailiac, thigh, midaxillary and the medial part of the leg) using skinfold caliper were recorded in the Excel format. It was determined that there was a significant difference (p